ANALISIS LABA RUGI DEPARTEMENT ROOM SALES PADA SELYCA MULIA HOTEL SAMARINDA - -, HARIS MASR (EKONOMIA, 2018)
Profit and Loss Analysis Department Sales Department At Selyca Mulia Hotel Samarinda. The purpose of this study is to determine the allocation of joint costs, profit sales room, the contribution of each type of room to the profit department department room sales at Selyca Mulia Hotel Samarinda.The formulation of the problem of this study is whether the allocation of shared costs contribute to the determination of profit department department sales room in each room type in Selyca Mulia Hotel Samarinda, whether the profit use of the room has reached the target profit determined and Which type of room at Selyca Mulia Hotel Samarinda contributed the most profit big in department room sales.The theoretical basis of this study is management accounting, referring to joint costs, income statement room. The hypothesis of this research is the allocation of cost together with the method of relative selling value contribute in the determination of profit departement room sales in every room type in Selyca Mulia Hotel Samarinda, the profit of the use of the room has reached the target profit and Deluxe Queen room type contributed profit department department sales highest at Selyca Mulia Hotel Samarinda.The analytical tool used in this research is the Profit and Loss Report of Department of Room and Cost Allocation Together With Relative Selling Value Method in each room type.Based on the calculation of the allocation of shared costs in the department room, it can be compiled income department department room sales reports on each type of room, so it can also count the operational cost (operating expenses) and departmental earnings (departmental income) each type of room in each May-July 2017 period. Average operational cost is 16% and department profit is on average 84% in May-July 2017. earnings department departments average 98.14% have reached target specified in period of May - July 2017. Based the results of the analysis proved that the method of cost allocation along with the relative selling value proved to contribute in the determination of profit. Also proven profit target department with an average achievement of 98.14%. The highest contribution of departmental profit in 3 periods is Deluxe Queen with average of 48.41% with 75.70% Oucupancy rate.